- Pemodelan Tarikan Perjalanan Komplek Perkantoran Terpadu Tenayan Raya - Lidno Fery hs; Leo Sentosa; Gunawan Wibisono (Racic : Rab Construction Research, 2026)
The Tenayan Raya Integrated Office Complex is the administrative center of the Pekanbaru City Government and is expected to undergo further development through the construction of new buildings and an increase in the number of employees. These changes will lead to higher trip attraction, which has the potential to affect traffic performance on Jalan Badak as the main access road. This study aims to model the magnitude of trip attraction. The dependent variable is Y (number of attracted trips), while the independent variables consist of X₁ (number of employees), X₂ (building floor area), X₃ (building site area), X₄ (parking area), X₅ (travel distance), X₆ (travel time), X₇ (floor area per employee ratio), and X₈ (employee per floor area ratio). The analytical method applied is Trip Generation using linear regression. The findings show that the number of employees (X₁) is the most influential variable affecting trip attraction. The best-fit model obtained is Y = 4.568 + 0.575X₁ with an R² value of 0.981.